Patient‐reported reasons for declining same‐day antiretroviral therapy initiation in routine HIV care settings in Lusaka, Zambia: results from a mixed‐effects regression analysis. Issue 7 (3rd July 2020) - Pry, Jake; Chipungu, Jenala; Smith, Helene J; Bolton Moore, Carolyn; Mutale, Jacob; Duran‐Frigola, Miquel; Savory, Theodora; Herce, Michael E
Abstract: Introduction: In the current "test and treat" era, HIV programmes are increasingly focusing resources on linkage to care and same‐day antiretroviral therapy (ART) initiation to meet UNAIDS 95‐95‐95 targets. After observing sub‐optimal treatment indicators in health facilities supported by the Centre for Infectious Disease Research in Zambia (CIDRZ), we piloted a "linkage assessment" tool in facility‐based HIV testing settings to uncover barriers to same‐day linkage to care and ART initiation among newly identified people living with HIV (PLHIV) and to guide HIV programme quality improvement efforts. Methods: The one‐page, structured linkage assessment tool was developed to capture patient‐reported barriers to same‐day linkage and ART initiation using three empirically supported categories of barriers: social, personal and structural. The tool was implemented in three health facilities, two urban and one rural, in Lusaka, Zambia from 1 November 2017 to 31 January 2018, and administered to all newly identified PLHIV declining same‐day linkage and ART. Individuals selected as many reasons as relevant. We used mixed‐ effects logistic regression modelling to evaluate predictors of citing specific barriers to same‐day linkage and ART, and Fisher's Exact tests to assess differences in barrier citation by socio‐demographics and HIV testing entry point. Results: A total of 1278 people tested HIV positive, of whom 126 (9.9%) declined same‐day linkage and ART, reporting a median of three barriers per respondent. Of these 126, 71.4% were female. Females declining same‐day ART were younger, on average, (median 28.5 years, interquartile range (IQR): 21 to 37 years) than males (median 34.5 years, IQR: 26 to 44 years). The most commonly reported barrier category was structural, "clinics were too crowded" (n = 33), followed by a social reason, "friends and family will condemn me" (n = 30). The frequency of citing personal barriers differed significantly across HIV testing point (χ 2 p  = 0.03). Significant predictors for citing ≥1 barrier to same‐day ART were >50 years of age (OR: 12.59, 95% CI: 6.00 to 26.41) and testing at a rural facility (OR: 9.92, 95% CI: 4.98 to 19.79). Conclusions: Given differences observed in barriers to same‐day ART initiation reported across sex, age, testing point, and facility type, new, tailored counselling and linkage to care approaches are needed, which should be rigorously evaluated in routine programme settings.